Combined use of fatty acid profile and fatty acid δ13C fingerprinting for origin traceability of scallops (Patinopecten yessoensis, Chlamys farreri, and Argopecten irradians). (15th November 2019) - Zhang, Xufeng; Han, Deming; Chen, Xiaojia; Zhao, Xinda; Cheng, Jinping; Liu, Yu
Highlights: 300 training samples and 75 testing samples from seven sites in China were collected. The combination of fatty acid profile and fatty acid δ 13 C fingerprinting was performed. The combination of these two methods enhanced the prediction capability (100%). The combination of two methods can be a promising tool for traceability of scallops. Abstract: The aim of this study was to evaluate the combination of fatty acid profile and fatty acid δ 13 C fingerprinting to identify the origins of scallops. Fatty acid contents, as well as fatty acid δ 13 C values of 300 samples of three scallop species ( Patinopecten yessoensis, Chlamys farreri, and Argopecten irradians ) from seven sites in China were determined. Principal component analysis was performed on datasets to evaluate their performance of classification. Moreover, 75 samples were tested by discrimination analysis to estimate the accuracy of origin prediction. The results show that the accuracy rate of fatty acid profile and fatty acid δ 13 C fingerprinting for origin prediction was 92% and 85.3%, respectively. The combination of these two methods improved the identification, with an accuracy rate of 100.0%. These results indicate that the combination of fatty acid profile and fatty acid δ 13 C fingerprinting can be a precise and promising tool for origin traceability of scallops.